Gene Expression Profile in Human Trabecular Meshwork From Patients With Primary Open-Angle Glaucoma - Liu, Yutao (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. To identify the specific genes in human trabecular meshwork (TM) related to POAG. METHODS. Primary open-angle glaucoma TM specimens were obtained from routine trabeculectomy surgery. Nonglaucomatous control TM specimens were dissected from donor eyes using the same approach as a standard trabeculectomy. All cases were screened for myocilin (MYOC) mutations. Total RNA was extracted, labeled, and hybridized to Illumina HumanWG-6 BeadChips. Expression data were normalized and analyzed using the R package limma in Bioconductor. Pathway analyses were performed using DAVID Bioinformatics Resources. RESULTS. Our study included surgical TM specimens from 15 cases and 13 controls. One case was identified with a heterozygous Q368X MYOC mutation. If TMs were available from both eyes in an individual, the expression data were combined for analysis. The following three comparisons were performed for differential analyses: (1) MYOC POAG case versus 14 non-MYOC POAG cases, (2) MYOC POAG case versus 13 controls, and (3) 14 non-MYOC POAG cases versus 13 controls. Limited by one MYOC case in comparisons 1 and 2, expression changes were reported comparing the fold changes but without P values. Comparison 3 identified 483 genes, including 36 components of TM exosomes. Gene ontology analysis identified several enriched functional clusters, including cell adhesion, extracellular matrix, and secretion. CONCLUSIONS. This is the largest TM expression study of POAG cases and controls performed to date and represents the first report of TM expression in a patient having POAG with a Q368X MYOC mutation. Our data suggest the potential role of endocytic and exosome pathways in the pathogenesis of POAG.